Stripe Rust Resistance in Aegilops tauschii Germplasm. Issue 5 (1st September 2013) - Liu, Miao; Zhang, Chaozhong; Yuan, Cuiling; Zhang, Lianquan; Huang, Lin; Wu, Jiajie; Wang, Jirui; Zheng, Youliang; Zhang, Huaigang; Liu, Dengcai; Fu, Daolin
ABSTRACT: Aegilops tauschii Coss., the D‐genome progenitor of hexaploid wheat ( Triticum aestivum L.), is an important source of useful genes for wheat improvement. We characterized a germplasm collection of 118 Ae. tauschii accessions for response to stripe rust, a devastating disease caused by the fungus Puccinia striiformis f. sp. tritici ( Pst ). We evaluated tillering stage and adult‐plant resistance to stripe rust using prevalent Pst races from the United States and China. Resistant accessions predominated in Ae. tauschii subsp. strangulata and Ae. tauschii subsp. tauschii from the Caspian Sea region. We further analyzed the inheritance of stripe rust resistance by inoculating F2 plants of 60 crosses with a mixture of Chinese Pst races. Crosses between resistant and susceptible lines indicated both dominant and recessive inheritance. Tests of allelism among 14 highly resistant accessions indicated the common presence of YrAS2388, previously mapped on chromosome arm 4DS, in all accessions. In conclusion, the study presented valuable data on stripe rust resistance in Ae. tauschii, which assist with informed introgression of the D‐genome trait for stripe rust resistance in common wheat.